Conversation Analysis (CA) as a tool for exploring interaction in an online video-conferencing based support service. Issue 3 (16th September 2019) - Chatwin, John; McEvoy, Phil
Abstract : Purpose: Around 60 per cent of people with dementia in the UK live at home. The experience of caring for a family member with dementia can be rewarding and positive, but it can also be significantly stressful. Current healthcare policy is encouraging greater provision to support family carers. Along with respite-care, day-care and support group-based initiatives, there has also been a focus on developing dementia-specific communication training. The paper discusses this issue. Design/methodology/approach: The authors outline a new initiative "Empowered Carers" which is being piloted in the North of England. Empowered Carers is an online support and communication training service for family carers who are caring for someone with dementia at home. It utilises online video conference-calling technology to connect carers with support workers, and also allows for simultaneous interactions involving other family members. A central tenet of the approach is a theoretically grounded support model, based on the concept of mentalisation. Findings: The authors describe the background to Empowered Carers, and how a conventional evaluation strategy for the initiative is being used alongside a socio-linguistic approach (Conversation Analysis – CA). This aims to provide empirical evidence about how the assimilation of mentalisation is reflected in the structuring of speech patterns in carers during support sessions. Originality/value: The authors explain the CA method, how it has been applied to similar talk-based therapeutic settings, and why its ability to explore sequential linguistic patterns across extremely large data-sets is particularly suited to studying interaction in emerging online arenas.